IMPLEMENTATION OF DIFFERENT CULTURES TO INFLUENCE POSTPARTUM DEPRESSION - Siti Nurhidayah (Departemen Psikiatri Fakultas Kedokteran Universitas Brawijaya, 2023)
Background: Postpartum depression (PPD) is a big problem that could cause effect adversely on postnatal mother’s mental health and cognitive and physical development for their children even though it is well known, disabling, and treatable. The prevalence of postpartum depression in the Middle East hasthe highest number(26%) but in contrast, Europe is on the lowest (8%). Postpartum practices traditionally are utilized for providing care to mothers. However, there are some evidence-based regarding particular outcomes of postpartum depression.Objective: To know about different cultures contributing to postpartum depression.Method: A literature review was conducted across 5 databases including PubMed, MEDLINE, PMC, Science Direct, and Taylor FrancisOnline between 2015 and 2021 which related particularly to cultural belief in postpartum and postpartum depression. The result will be determined by literature review.Results: There are a wide range of different culture that were implemented upon postpartum period in Western country and Asian Country resulting postpartum depression. Idealized mother, multitasking, having a good financial, job, bonding with infant, is emphasized in Western Country while Asian Country have certain culture in every region. However, gender is common in both nations to cause depressionConclusion: Postpartum depression is psychological disorder which can suffer during postpartum period culture is one of the included causes of it and gender preference is the most issue which lead postpartum depression. Keywords: cultures, postpartum, depression.